2015
DOI: 10.1139/cjm-2015-0341
|View full text |Cite
|
Sign up to set email alerts
|

Yeast microbiota of natural cavities of manatees (Trichechus inunguis and Trichechus manatus) in Brazil and its relevance for animal health and management in captivity

Abstract: The aim of this study was to characterize the yeast microbiota of natural cavities of manatees kept in captivity in Brazil. Sterile swabs from the oral cavity, nostrils, genital opening, and rectum of 50 Trichechus inunguis and 26 Trichechus manatus were collected. The samples were plated on Sabouraud agar with chloramphenicol and incubated at 25 °C for 5 days. The yeasts isolated were phenotypically identified by biochemical and micromorphological tests. Overall, 141 strains were isolated, of which 112 were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…These isolates were recovered on Petri dishes containing Sabouraud dextrose 2% agar plus chloramphenicol (0.05 g/L), and identified through phenotypical characteristics, such as macromorphological and micromorphological analyses and biochemical tests, including urease production, carbohydrate and nitrogen assimilation and carbohydrate fermentation. The identification of cryptic specie (Candida albicans-Candida dubliniensis and Candida parapsilosis species Complex) was confirmed through molecular analyses (Sidrim et al 2015). The recovered Candida isolates are kept in the culture collection of the Specialized Medical Mycology Center (CEMM) and belong to the following species: C. albicans (52/105), C. parapsilosis sensu stricto (14/105), Candida orthopsilosis (4/105), Candida metapsilosis (3/105), Candida guilliermondii (12/105), Candida pelliculosa (3/105), Candida tropicalis (6/105), Candida glabrata (2/105), Candida famata (5/105), Candida ciferri (1/105), Candida norvegensis (1/105), and Candida krusei (2/105).…”
Section: Yeastsmentioning
confidence: 90%
See 2 more Smart Citations
“…These isolates were recovered on Petri dishes containing Sabouraud dextrose 2% agar plus chloramphenicol (0.05 g/L), and identified through phenotypical characteristics, such as macromorphological and micromorphological analyses and biochemical tests, including urease production, carbohydrate and nitrogen assimilation and carbohydrate fermentation. The identification of cryptic specie (Candida albicans-Candida dubliniensis and Candida parapsilosis species Complex) was confirmed through molecular analyses (Sidrim et al 2015). The recovered Candida isolates are kept in the culture collection of the Specialized Medical Mycology Center (CEMM) and belong to the following species: C. albicans (52/105), C. parapsilosis sensu stricto (14/105), Candida orthopsilosis (4/105), Candida metapsilosis (3/105), Candida guilliermondii (12/105), Candida pelliculosa (3/105), Candida tropicalis (6/105), Candida glabrata (2/105), Candida famata (5/105), Candida ciferri (1/105), Candida norvegensis (1/105), and Candida krusei (2/105).…”
Section: Yeastsmentioning
confidence: 90%
“…All animals received a single clinical score (poor, medium, good, or excellent) considering the nutritional status, presence of external lesions, clinical history and use of antimicrobials. Regarding T. inunguis, 88% (44/50) of the animals received excellent score, 8% (4/50) good and 4% (2/50) medium score, while 69.3% (18/26) T. manatus received excellent clinical score, 11.5% (3/26) good, 11.5% (3/26) medium, and 7.7% (2/26) poor (Sidrim et al 2015). Conditions for maintenance in captivity also varied, such as water treatment (chlorinated or untreated), salinity (salt or fresh) and density of animals per tank.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic investigation to characterize the yeast microbiota of captive Amazonian manatees detected at least 12 different species of Candida in their natural cavities (oral cavity, nostrils, genital opening, and rectum), and the occurring rates seemed to be proportional to the number of individuals kept in each pool (Sidrim et al, 2015). Investigation of these microorganisms' resistance to antifungal susceptibility tests revealed that C. albicans, C. tropicalis, and C. guilliermondii were resistant to itraconazole and fluconazole (Sidrim et al, 2016).…”
Section: Dietmentioning
confidence: 99%
“…Em estudo conduzido por Sidrim et al [52] sobre as leveduras da microbiota das cavidades naturais (oral, nasal, genital e retal) em peixes-bois de…”
Section: Fúngicaunclassified